Influence of the Static Loading of a Raft Unconnected to a Pile on the Pile Displacements Tested in Field Conditions - Sedin, Vladimir; Bikus, Kateryna; Kovba, Vladyslav; Kononov, Denys; Zahilskyi, Vitalii (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
We present the results of a static pile-raft interaction test in field conditions. The pile and the raft were unconnected. The static loading on the raft affected the displacements of the pile due to the skin friction. The displacements were also observed for another pile, placed at the 3-metre distance.
Keywords: pile foundation; static loading; friction forces; raft; fundament palowy; obciążenia statyczne; siły tarcia